Sulfite-Promoted C–H Fluoroalkyl Sulfuration of Imidazoheterocycles with Bromofluoroacetate and Elemental Sulfur - Gao, Yong-Chao; Huang, Zi-Hao; Zhang, Zhao-Sheng; Xie, Jin-Xin; Cui, Zi-Ning; Tang, Ri-Yuan (Synthesis, 2020)
A transition-metal-free sulfite-promoted three-component C–H sulfuration between imidazoheterocycles, elemental sulfur, and bromofluoroacetate is developed. Sulfites, including Na2S2O4, NaHSO3, and Na2S2O3, are able to promote the formation of two C–S bonds in one step using elemental sulfur as a green sulfurating agent, allowing the rapid introduction of the synthetically useful S-fluoroacetate group into imidazoheterocycles. These new imidazoheterocycle derivatives bearing an S-fluoroacetate group can be easily modified to produce pharmaceutically attractive compounds.
Keywords: sulfites; sulfides; elemental sulfur; C–H functionalization; imidazoles